Esophageal Endoscopic Submucosal Dissection Assisted by an Overtube with a Traction Forceps: An Animal Study - Ken Ohata; Kuangi Fu; Eiji Sakai; Kouichi Nonaka; Tomoaki Tashima; Yohei Minato; Akiko Ohno; Takafumi Ito; Yosuke Tsuji; Hideyuki Chiba; Makoto Yamawaki; Hideyuki Hemmi; et al. (Gastroenterology Research and Practice)
Esophageal endoscopic submucosal dissection (ESD) is technically difficult. To make it safer, we developed a novel method using overtube with a traction forceps (OTF) for countertraction during submucosal dissection. We conducted an ex vivo animal study and compared the clinical outcomes between OTF-ESD and conventional method (C-ESD). A total of 32 esophageal ESD procedures were performed by four beginner and expert endoscopists. After circumferential mucosal incision for the target lesion, structured as the isolated pig esophagus 3 cm long, either C-ESD or OTF-ESD was randomly selected for submucosal dissection. All the ESD procedures were completed as en bloc resections, while perforation only occurred in a beginner’s C-ESD procedure. The dissection time for OTF-ESD was significantly shorter than that for C-ESD for both the beginner and expert endoscopists (22.8±8.3 min versus 7.8±4.5 min, P<0.001, and 11.3±4.4 min versus 5.9±2.5 min, P=0.01, resp.). The frequency and volume of the submucosal injections were significantly smaller for OTF-ESD than for C-ESD (1.3±0.6 times versus 2.9±1.5 times, P<0.001, and 5.3±2.8 mL versus 15.6±7.3 mL, P<0.001, resp.). Histologically, muscular injury was more common among the C-ESD procedures (80% versus 13%, P=0.009). Our results indicated that the OTF-ESD technique is useful for the safe and easy completion of esophageal ESD.